Study of the Processes of Destruction of Rocks under the Action of Hydrodynamic Pressure - Aliyarova, Kh.E. (Herald of Azerbaijan Engineering Academy, 2025)
The purpose of using hydro-mechanization in the mining industry is to ensure the crushing of large parts of the rock mass and solid phase to sizes suitable for hydraulic transportation condi-tions. This process requires the creation of sufficient pressure in the water flow. Therefore, the required pressure and water flow rate must be determined in advance. For this purpose, various mathematical models were analyzed to determine the parameters, relevant research studies were studied, and the most realistic ones were selected from the results. Practical calculations were car-ried out to determine the parameters, and graphs were drawn up based on the results. The results obtained allow determining the pressure and flow rate required to crush the rock to the required size.